MONITORING SISTEM PROTEKSI KEBAKARAN AKTIF PADA PLTU ANGGREK 2 X 25 MW - Pido, Rifaldo; Boli, Rahmad Hidayat; Rifal, Mohamad (Journal Of Renewable Energy Engineering, 2024)
The Anggrek Unit Steam Power Plant (PLTU) is a power generation facility whose construction began in 2007 and began operating in 2019 with a capacity of 2 x 25 MW. Since its inauguration, PLTU Anggrek has become one of the main sources of electricity distribution in Gorontalo Province, so the frequency of power outages in the area has now decreased significantly. The water supply system for fire fighting uses BSP pipes. In this research, the aim is to determine the active fire protection system. This research was carried out with a qualitative descriptive design with data collection: observation and interviews. The assessment of the results of existing suitability will be assessed using descriptive percentage calculations. The research results show that of the 7 variables discussed, the average value for the level of fulfillment is 98.57%. Based on the level of fire audit assessment that meets the requirements of Indonesian national standards and international standards, the results are in the Good criteria or have met the requirements.